A Retrospective Study in Adults with Metabolic Syndrome: Diabetic Risk Factor Response to Daily Consumption of Agaricus bisporus (White Button Mushrooms) - Calvo, Mona S.; Mehrotra, Anita; Beelman, Robert B.; Nadkarni, Girish; Wang, Lingzhi; Cai, Weijing; Goh, Boon Cher; Kalaras, Michael D.; Uribarri, Jaime (Plant foods for human nutrition (Dordrecht), 2016)
Adults with metabolic syndrome from different race/ethnicities are often predisposed to developing type 2 diabetes (T2D); however, growing evidence suggests that healthy diets and lifestyle choices can significantly slow or prevent progression to T2D. This poorly understood relationship to healthy dietary patterns and prevention of T2D motivated us to conduct a retrospective analysis to determine the potential impact of a minor dietary lifestyle change (daily mushroom consumption) on known T2D risk factors in racially diverse adults with confirmed features of the metabolic syndrome. Retrospectively, we studied 37 subjects who had participated in a dietary intervention focused on vitamin D bioavailability from white button mushrooms (WBM). All 37 had previously completed a 16-week study where they consumed 100 g of WBM daily and were then followed-up for one month during which no mushrooms were consumed. We analyzed differences in serum risk factors from baseline to 16-week, and from baseline to one-month follow-up. Measurement of serum diabetic risk factors included inflammatory and oxidative stress markers and the antioxidant component naturally rich in mushrooms, ergothioneine. Significant beneficial health effects were observed at 16-week with the doubling of ergothioneine from baseline, increases in the antioxidant marker ORAC (oxygen radical absorption capacity) and anti-inflammatory hormone, adiponectin and significant decreases in serum oxidative stress inducing factors, carboxymethyllysine (CML) and methylglyoxal (MG), but no change in the lipid oxidative stress marker 8-isoprostane, leptin or measures of insulin resistance or glucose metabolism. We conclude that WBM contain a variety of compounds with potential anti-inflammatory and antioxidant health benefits that can occur with frequent consumption over time in adults predisposed to T2D. Well-controlled studies are needed to confirm these findings and identify the specific mushroom components beneficial to health.